2021
DOI: 10.24893/jkma.v15i2.656
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Visual Attention Among Smoker and Non-Smoker by Using Human Eye Tracker of Health Graphic Warning on Tobacco Package

Abstract: pada bungkus rokok telah dilakukan bertahun-tahun di Indonesia. Akan tetapi, jumlah perokok di Indonesia tidak mengalami penurunan yang menggembirakan. Berbagai studi terkait persepsi perokok terhadap Gambar Peringatan Kesehatan yang didasarkan pada metode wawancara memberikan hasil yang berbeda-beda. Penelitian ini menganalisis bagaimana atensi visual para perokok saat melihat bungkus rokok dan dibandingkan dengan para non perokok dengan menggunakan teknologi human eye tracker. Remaja berusia 18 -20 tahun yan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although the influence can be produced by pictures of smoking-related diseases on cigarette packs, it turns out that the most significant source of the desire to quit smoking comes from within oneself in the form of perceived behavioral control. Other exciting data state that when health warning images are shown to active smokers, almost half of the active smokers expressed no fear of the diseases that can arise from smoking (Edison, Anisa and Fauzy, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the influence can be produced by pictures of smoking-related diseases on cigarette packs, it turns out that the most significant source of the desire to quit smoking comes from within oneself in the form of perceived behavioral control. Other exciting data state that when health warning images are shown to active smokers, almost half of the active smokers expressed no fear of the diseases that can arise from smoking (Edison, Anisa and Fauzy, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that smokers and non-smokers have very different attention when looking at cigarette packs, whereas non-smokers will focus on smoking-related diseases. In contrast, smokers will focus on cigarette logos (Edison, Anisa and Fauzy, 2021). This study aims to evaluate the reactions and perceptions of adults to pictorial warning labels by measuring eyetracking devices and knowing their relationship to smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, death cases due to smoking behavior reached 235,000 people each yearand of the number of deaths due to smoking, 25,000 of them are individuals who do not have smoking habits (Edison et al, 2021). The high number of smoking deaths is undoubtedly caused by the number of individuals who have smoking habits in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…(Punde et al, 2017).In addition, the human eye tracker can also be used to find out what smokers see when images of cigarette packs are displayed, where smokers tend to focus on cigarette brands, while nonsmokers focus more on health graphic warning images. (Edison et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were sitting on chairs in a relaxed condition with a distance of 60 -70 cm from the monitor screen to their eyes. During recording, participants were asked to minimize head movement (Figure 1), while the room lighting was set not too bright or dim (Edison et al, 2021). Before recording, the HET instrument calibration was carried out to ensure the precision of the eye position against the object seen on the monitor screen.…”
Section: Methodsmentioning
confidence: 99%